Incessant ovulation: a review of its importance in predicting cancer risk - Cramer, Daniel W. (Frontiers in Oncology, 2023)
Estrous cycles are recurring changes in therian mammals induced by estrogen, progesterone, and other hormones culminating in endometrial proliferation, ovulation, and implantation if fertilization occurred. In women, the estrous cycle is the menstrual cycle; but, unlike most mammals, the end of an infertile cycle is marked by endometrial sloughing and start of another without an anestrous phase. Women stop cycling at menopause while, in most mammals, cycles continue until death. Epidemiologic studies identified menarche, menopause, births, lactation, and oral contraceptive (OC) use as key risk factors for ovarian, breast, and endometrial cancers. A composite variable was created to estimate the number of cycles not interrupted by events that stop ovulation. Captured by the phrase, “incessant ovulation,” repetitive cycles were first postulated to affect ovarian cancer risk and later extended to breast and endometrial cancer. These associations could be explained by cumulative effects of repetitive tissue changes within reproductive organs, immune consequences of repetitive ovulation through the glycoprotein Mucin 1, and residual effects of past ovulations that enhance ovarian production of testosterone. The latter two pathways could affect risk for cancers in other organs not considered “reproductive.”